’idārāt ǧadīdah lil-tanqīb fī Mārī wa-natā’iǧuhā ’l-’ūlā - Mārġarūn, Ǧān
Jean(-Claude) Margueron; New Directions for Excavation at Mari and their First Results; ersch. 1986?; in Arabic, translated and abridged by Baš?r Zuhd?.